The Influence of Women's Autonomy on the Decision to Seek Antenatal Care K4 and K6 - Loviyanti, Dhea Monica; Handayani, Dwini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study analyses the influence of women's autonomy on the decision to attend antenatal care at K4 and K6 levels in Indonesia, using data from the 2017 Indonesia Demographic and Health Survey (IDHS). A binary logistic regression model was used to explore the influence of women's autonomy—measured through decision-making power within the household and control over resources—on the utilisation of maternal health services. Control variables include age, education, women's employment status, husband's employment status and education, place of residence (urban/rural), and geographical region (Java-Bali vs. non-Java-Bali). The results indicate that women's autonomy significantly increases the likelihood of attending antenatal visits according to the K4 and K6 standards. These findings are consistent across various model specifications, both with and without additional control variables.